COVID-19 and children with congenital anomalies: a European survey of parents' experiences of healthcare services. Issue 7 (19th July 2022) - Latos-Bieleńska, Anna; Marcus, Elena; Jamry-Dziurla, Anna; Rankin, Judith; Barisic, Ingeborg; Cavero- Carbonell, Clara; Den Hond, Elly; Garne, Ester; Genard, Lucas; João Santos, Ana; Lutke, L Renée; Matias Dias, Carlos; et al.
Abstract : Objective: To survey parents and carers of children with a congenital anomaly across Europe about their experiences of healthcare services and support during the COVID-19 pandemic. Design: Cross-sectional study. Setting: Online survey in 10 European countries, open from 8 March 2021 to 14 July 2021. Population: 1070 parents and carers of children aged 0–10 years with a cleft lip, spina bifida, congenital heart defect (CHD) requiring surgery and/or Down syndrome. Main outcome measures: Parental views about: the provision of care for their child (cancellation/postponement of appointments, virtual appointments, access to medication), the impact of disruptions to healthcare on their child's health and well-being, and satisfaction with support from medical sources, organisations and close relationships. Results: Disruptions to healthcare appointments were significantly higher (p<0.001) in the UK and Poland, with approximately two-thirds of participants reporting 'cancelled or postponed' tests (67/101; 256/389) and procedures compared with approximately 20% in Germany (13/74) and Belgium/Netherlands (11/55). A third of participants in the UK and Poland reported 'cancelled or postponed' surgeries (22/72; 98/266) compared with only 8% in Germany (5/64). In Poland, 43% (136/314) of parents reported that changes to their child's ongoing treatment had moderately to severely affected their child's health, significantly higher than all other countries (p<0.001). Satisfaction ratings for support from general practitioners were lowest in the UK and Poland, and lowest in Poland and Italy for specialist doctors and nurses. Conclusion: A large proportion of participants reported disruptions to healthcare during the pandemic, which for some had a significant impact on their child's health. Regional differences in disruptions raise questions about the competence of certain healthcare systems to meet the needs of this vulnerable group of patients and indicate improvements should be strived for in some regions.